Mining for Change Natural Resources and Industry in Africa - Page, John; Tarp, Finn (Oxford University Press, 2020)
For a growing number of countries in Africa the discovery and exploitation of natural resources is a great opportunity, but one accompanied by considerable risks. In Africa, countries dependent on oil, gas, and mining have tended to have weaker long-run growth, higher rates of poverty, and greater income inequality than less resource-abundant economies. In resource-producing economies, relative prices make it more difficult to diversify into activities outside of the resource sector, limiting structural change. Economic structure matters for at least two reasons. First, countries whose exports are highly concentrated are vulnerable to declining prices and volatility. Second, economic diversification matters for long-term growth. This book presents research undertaken to understand how better management of the revenues and opportunities associated with natural resources can accelerate diversification and structural change in Africa. It begins with chapters on managing the boom, the construction sector, and linking industry to the resource-three major issues that frame the question of how to use natural resources for structural change. It then reports the main research results for five countries-Ghana, Mozambique, Uganda, Tanzania, and Zambia. Each country study covers the same three themes-managing the boom, the construction sector, and linking industry to the resource. One message that clearly emerges is that good policy can make a difference. A concluding chapter sets out some ideas for policy change in each of the areas that guided the research, and then goes on to propose some ideas for widening the options for structural change.